Evaluation of Absolute Lymphocyte Count at Diagnosis and Mortality Among Patients With Localized Bone or Soft Tissue Sarcoma - Brewster, Ryan (JAMA Netw Open, 2021)
IMPORTANCE: Host-related immune factors have been implicated in the development and progression of diverse malignant neoplasms. Identifying associations between immunologic laboratory parameters and overall survival may inform novel prognostic biomarkers and mechanisms of antitumor immunity in localized bone and soft tissue sarcoma. OBJECTIVE: To assess whether lymphopenia at diagnosis is associated with overall survival among patients with localized bone and soft tissue sarcoma. DESIGN, SETTING, AND PARTICIPANTS: This retrospective cohort study analyzed patients from the Stanford Cancer Institute with localized bone and soft tissue sarcoma between September 1, 1998, and November 1, 2018. Patients were included if laboratory values were available within 60 days of diagnosis and, if applicable, prior to the initiation of chemotherapy and/or radiotherapy. Statistical analysis was performed from January 1, 2019, to November 1, 2020. EXPOSURES: Absolute lymphocyte count within 60 days of diagnosis and antimicrobial exposure, defined by the number of antimicrobial agent prescriptions and the cumulative duration of antimicrobial administration within 60 days of diagnosis. MAIN OUTCOMES AND MEASURES: The association between minimum absolute lymphocyte count at diagnosis and 5-year overall survival probability was characterized with the Kaplan-Meier method and multivariate Cox proportional hazards regression models. Multivariable logistic regressions were fitted to evaluate whether patients with lymphopenia were at greater risk of increased antimicrobial exposure. RESULTS: Among 634 patients, the median age at diagnosis was 53.7 years (interquartile range, 37.5-66.8 years), and 290 patients (45.7%) were women, with a 5-year survival probability of 67.9%. There was a significant inverse association between lymphopenia at diagnosis and overall survival (hazard ratio [HR], 1.82; 95% CI, 1.39-1.40), resulting in a 13.5% 5-year survival probability difference compared with patients who did not have lymphopenia at diagnosis (60.2% vs 73.7% for those who never had lymphopenia). In addition, poorer survival was observed with higher-grade lymphopenia (grades 3 and 4: HR, 2.44; 95% CI, 1.68-3.55; grades 1 and 2: HR, 1.60; 95% CI, 1.18-2.18). In an exploratory analysis, patients with increased antibiotic exposure were more likely to have lymphopenia (odds ratio, 1.96; 95% CI, 1.26-3.07 for total number of antimicrobial agents; odds ratio, 1.70; 95% CI, 1.10-2.57 for antimicrobial duration) than antimicrobial-naive patients. CONCLUSIONS AND RELEVANCE: This study suggests that an abnormally low absolute lymphocyte count at diagnosis is associated with higher mortality among patients with localized bone and soft tissue sarcoma; therefore, lymphopenia may serve as a reliable prognostic biomarker. Potential mechanisms associated with host immunity and overall survival include a suppressed antitumor response and increased infectious complications, which merit future investigation.